IMPLEMENTATION OF ILMI INTERPRETATION IN QUR'AN SCIENCE SUBJECT AT ISLAMIC JUNIOR HIGH SCHOOL TAHFIZH RABBANIY PEKANBARU - Nasrul Fatah; Hidayatullah Ismail (SYAHADAH : Jurnal Ilmu al-Qur'an dan Keislaman, 2023)
As a book of guidance, the Qur'an requires itself to be adaptive to the changes and developments of the times including science and technology. Including in the study of interpretation of the Qur'an which gave birth to various studies of interpretation with a scientific approach or science which is then known as ilmi interpretation. The spirit of integration of the Qur'an with science gave birth to various works both written and the birth of educational institutions that seek to realize the integration. So this research intends to portray the implementation of ilmi interpretation in learning Qur'an science at Junior High School Tahfizh Rabbaniy Pekanbaru. This research is field research and is qualitative in nature with data collection techniques of interviews, observation and documentation. From this research, it is found that the learning of Qur'anic science at Junior High School Tahfizh Rabbaniy Pekanbaru has applied the ilmi interpretation approach although it is still relatively simple by utilizing the findings and theories that already exist. Coupled with the limitations of minimal supporting facilities, the practicum for proving existing theories is very limited. However, this is a positive step to introduce the study of ilmi interpretation at the level of secondary education.